Merges and acquisitions and the resultant ramifications on employees in the transaction. a study of South Africa's Section 197 Labour Relations Act 1995 as amended in 2002 - Ndungu, Herbert Mburu (School For Advanced Legal Studies, 2025)
Business organizations engage in mergers and acquisitions (M&As) to accomplish various objectives, including, but not limited to, increasing growth potential, expanding product lines, entering new markets at a faster speed, eliminating competitors gaining access to intellectual capital and gaining desired technologies. 1 M&As have lately also been undertaken as a means of business reorganization.